EFFECT OF ASTRAGALOSIDE ON VITAMIN D-RECEPTOR EXPRESSION AFTER ENDOTHELIN-1-INDUCED CARDIOMYOCYTE INJURY - yunzhi, Chen; jiaxu, Chen; jie, Gao; yihui, Chai; wen, Li; zhong, Qin (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Astragaloside, which is one of the main components of Astragalus membranaceus, has been widely used in the treatment of congestive heart failure in China, and it can protect cardiomyocytes. Its mechanism of action remains unclear. Therefore, the present study was carried out to investigate the influence of astragaloside on rat cardiomyocytes stimulated with endothelin-1 (ET-1), and explored the underlying mechanism.Materials and Methods: ET-1 was used to stimulate primary rat cardiomyocytes and establish a cardiomyocyte hypertrophy model. Different astragaloside doses were administered in combination with ET-1. Cardiomyocyte hypertrophy and apoptosis were examined using transmission electron microscopy (TEM) and flow cytometry, respectively. The molecular mechanism was explored by analyzing the mRNA of the vitamin D receptor (VDR), cytochrome P450 family 27 subfamily B member 1(CYP27B), cytochrome P450 family 24 subfamily A member 1(CYP24A) and renin mRNA levels by quantificational real-time polymerase chain reaction(qRT-PCR).Results: Rat cardiomyocyte hypertrophy model was established successfully. Astragaloside administration significantly affected cell apoptosis and significantly inhibited ET-1-induced cardiomyocyte hypertrophy in a dose-dependent manner. Astragaloside treatment affected the expression of signaling molecules in the vitamin D axis.Conclusion: Astragaloside inhibits ET-1-induced cardiomyocyte hypertrophy. This effect can be reversed by regulating the levels of the relevant factors in the vitamin D axis.